Souffles-Anfas : a critical anthology from the Moroccan journal of culture and politics - Harrison, Olivia C., 1980-; Harrison, Olivia C., 1980-; Villa-Ignacio, Teresa, 1975-; Villa-Ignacio, Teresa, 1975- (Stanford University Press, 2016)
"The essays, poems, and artwork included in this anthology--by the likes of Abdelkebir Khatibi, Tahar Ben Jelloun, Albert Memmi, Etel Adnan, Sembene Ousmane, René Depestre, and Mohamed Melehi--offer a unique window into the political and artistic imaginaries of writers and intellectuals from the Global South."